Implementasi Pencegahan Maladministrasi Pelayanan Publik Oleh Ombudsman Republik Indonesia - Andi Setiawan (Publikasi Indonesia, 2023)
This study discusses about the implementation of Indonesia Ombudsman’s maladministration prevention action at public service sector in the era of covid-19 pandemic along with the resisting and supporting factor. Researcher used George III’s theory about policy implementation with its four indicators, those are communication, resource, dispositions, and bureaucratic structure. The result of this study indicates that even though maladministration prevention action has keep going during the pandemic, there are some obstacles that made the program did not run effectively. This matter can be seen from lack of human resource and the pandemic situation that limit the movement of Indonesia Ombudsman. This makes Indonesia Ombudsman’s action itself become slower than usual. Budget problem also can be seen because Ombudsman’s budget got decreased because of the pandemic situation where the government allocates most of their funds for handling the pandemic. Despite all those problems, all of Indonesia Ombudsman’s employees always try to work as hard as they can, according to the procedure to maintain Indonesia Ombudsman’s quality.